Algorithms in C. Part 5 : graph algorithms - Sedgewick, Robert (Addison-Wesley, 2002)
(Pearson Education) Text providing a comprehensive introduction to important algorithms in C, concentrating on graph algorithms. Covers diagraphs and DAGs, shortest paths, minimum spanning trees, network flows, sample C code, and detailed algorithm descriptions. Previous edition not cited. Softcover. DLC: C (Computer program language).
Keywords: datová struktura; přírodní vědy